Phytoremediation of batik industry wastewater using water hyacinth plant as a medium for maintaining Cyprinus Carpio L. - Hadi Susilo; Swastika Oktavia; Roudotussaadah Roudotussaadah (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2021)
Batik is one of Indonesia's cultural heritage that has been recognized internationally. Currently, public demand for batik continues to increase, increasing the production of the batik industry in Banten and will be the impact of increasing batik liquid waste. The results of batik production waste are usually directly disposed of through public water channels without being treated first. This condition can cause environmental pollution that will disrupt the sustainability of aquatic ecosystems. The purpose of this study was to determine the effect of phytoremediation of batik industrial wastewater on the lethality and structure of Cyprinus Carpio L. scales. This study used a completely randomized design with 5 treatments and 3 repetitions. The treatment used was the maintenance of Cyprinus Carpio L. in the wastewater from the phytoremediation batik industry with concentrations of 0%, 5%, 10%, 20%, and 40%. The results showed that phytoremediation using water hyacinth plants reduced the BOD and COD content of batik waste. Phytoremediation of batik waste affects the lethality of Cyprinus Carpio L. and the structure of the scales. At concentrations of 20% and 40%, the highest average percentage of lethality is 60% death. Fish mortality is characterized by changes in behavior such as movement activity, body balance, and color morphology. The concentration of the batik industry wastewater also affects the amount of lethality and the sublethal effect of Cyprinus Carpio L. The attachment of the waste indicates the sublethal effect to the scales, the highest concentration of which is 20% and 40%, respectively.